Psychological aspects of press reports vs. actual possibilities of genetic testing in oncology - Litwiniuk, Maria; Karolczak, Grażyna; Bręborowicz, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2006)
Breast cancer is the most common cancer in women in Poland. Although the incidence rate is constantly increasing, breast cancer mortality has recently been stable. This phenomenon may be explained by combined benefits of better treatment and early detection. The extensive amount of information about breast cancer and mammography conveyed by the media has undoubtedly played an important role in this process. However, some doubts arise when it comes to press information about genetic testing. The aim of the study was to indicate the problems resulting from unsatisfactory press information about genetic testing. With improper information women who have been tested negative may no longer be interested in prophylactic mammography, while patients with a positive result, if deprived of prior counselling, may experience psychological distress. It should be once again stressed that patients should first be offered full information and counselling, and that the decision to have a genetic test performed should only be made after the general information about breast cancer as well as the medical, psychological and social implications of a positive genetic test result has been given.